Investigating the cardioprotective effects of Fuzheng Yangxin recipe based on network pharmacology and experimental evaluation - Wang, Anzhu; Zhao, Wei; Yan, Kaituo; Guo, Lijun; Gao, Feng; Chen, Jingjing; Wang, Yifei; Ma, Xiaochang (Frontiers in Pharmacology, 2022)
Background: Under Chinese medicine theory guidance, Fuzheng Yangxin Recipe (FZYX) is clinically effective for the treatment of heart failure (HF) caused by ischemic heart disease (IHD). This study aimed to investigate the mechanism of the myocardial protective effects of FZYX on HF.Materials and methods: The Gene expression omnibus database was used to identify differential genes of the IHD subtype. Through network pharmacological methods, the targets of the active components of FZYX were obtained.We also constructed IHD-induced HF model rats by ligating the left anterior descending coronary artery. Echocardiography, pathological section staining, enzyme-linked immunosorbent assay, western blotting, immunohistochemistry, and quantitative real-time PCR analyses were performed to verify the protective effects of FZYX on the myocardium.Results: We identified 53 active components and 37 potential targets of FZYX associated with the IHD subtype. Signal transducer and activator of transcription 3 (STAT3) is a key protein in the protein-protein interaction (PPI) network. A total of 146 biological processes, 10 cellular components and 40 molecular function subcategories were identified by Gene Ontology (GO) enrichment analysis, and 18 signalling pathways, including apoptosis, were identified by Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis. In vivo experiments showed that FZYX significantly inhibited cardiomyocyte apoptosis, promoted the expression and phosphorylation of STAT3, and improved cardiac function. Conclusions: FZXY improves cardiac function and protects cardiomyocytes from injury via multi-component, multi-target and multi-pathway action, especially its possible role in regulating STAT3 expression and anti-apoptotic effect.